Transesterification Reaction from Rice Bran Oil to Biodiesel over Heterogeneous Base Calcium Oxide Nanoparticles Catalyst - Nur Fatin Sulaiman; Abdul Rahim Yacob; Siew Ling Lee (Science and Technology Indonesia, 2020)
This research focused on the use of heterogeneous base catalyst, calcium oxide (CaO), an alkaline earth metal oxide to produce biodiesel. The aim of this research is to investigate the potential of commercial calcium carbonate, CM-CaCO3 to be transformed to nanostructured CaO and further used as a heterogeneous base catalyst for single step transesterification of rice bran oil to biodiesel. The CaO samples were calcined at temperatures of 100°C to 700°C under vacuum at 10-3 mbar. TGA-DTA result displayed that the calcination temperature for CM-CaCO3 to form CaO must be higher than 600°C. This was supported by FTIR results which indicated the complete formation of CaO at 700°C. XRD showed the rhombohedral CaCO3 and hexagonal Ca(OH)2 were totally disappeared, leaving only crystalline cubic CaO at 700oC. Interestingly, CaO obtained at 700°C (CaO-700) showed the larger BET surface area and highest basicity with 11.5 m2g-1 and 1.959 mmol/g, respectively. The prepared nanostructured CaO-700 was selected and applied for single step transesterification reaction of rice bran oil to produce biodiesel. NMR and GC-FID results further confirmed that biodiesel was successfully formed using CaO-700 as catalyst.